Silencing of ANGPTL8 Alleviates Insulin Resistance in Trophoblast Cells - Bai, Yu; Du, Qiang; Zhang, Le; Li, Ling; Wang, Nana; Wu, Bo; Li, Ping; Li, Ling (Frontiers in Endocrinology, 2021)
This study aims to investigate the effect of angiopoietin like 8 (ANGPTL8) on gestational diabetes mellitus (GDM) and insulin resistance (IR). The GDM model was induced by high fat diet in mice, and IR was observed. The expression and secretion of ANGPTL8 were promoted in placenta of GDM mice. IR was induced in trophoblast cell HTR-8/SVneo by treatment of high concentration of insulin, and the expression levels of ANGPTL8 were increased. Silencing of ANGPTL8 alleviated IR and decreased glucose uptake in HTR-8/SVneo cells. However, the inflammation and oxidative stress in IR cells were not restrained by ANGPTL8 knockdown. In addition, c-Jun N-terminal kinase (JNK) signaling was activated by IR, which was inhibited by silencing of ANGPTL8. The effect of ANGPTL8 knockdown on IR was attenuated by JNK antagonist, and aggravated by JNK agonist, suggesting that ANGPTL8 affected IR by regulating JNK signaling. In conclusion, we demonstrated that the silencing of ANGPTL8 ameliorated IR by inhibiting JNK signaling in trophoblast cells. These findings may provide novel insights for diagnosis and treatment of GDM in clinic.